Biomimetics - Habib, Maki K.; Martín-Gómez, César (IntechOpen, 2021)
Bioinspired systems, technologies and techniques known as "biomimetics" or the "mimicry of nature," represent a ground-breaking method of scientific research based on innovation and a creative design approach of the 'nature' laboratory to be applied to any scientific discipline. This approach and the associated way of thinking facilitates the cross-fertilization of scientific fields, integrating biology and the interdisciplinary knowledge featuring the evolution of models that have refined in nature within any scientific discipline.